Antidiabetic Activity of Elephant Grass (Cenchrus Purpureus (Schumach.) Morrone) via Activation of PI3K/AkT Signaling Pathway, Oxidative Stress Inhibition, and Apoptosis in Wistar Rats - Ojo, Oluwafemi Adeleke; Oni, Abosede Itunuoluwa; Grant, Susan; Amanze, Jennifer; Ojo, Adebola Busola; Taiwo, Odunayo Anthonia; Maimako, Rotdelmwa Filibus; Evbuomwan, Ikponmwosa Owen; Iyobhebhe, Matthew; Nwonuma, Charles Obiora; Osemwegie, Omorefosa; Agboola, Anthonia Oluyemi; et al. (Frontiers in Pharmacology, 2022)
Ethnopharmacological Relevance: The management of diabetes over the years has involved the use of herbal plants, which are now attracting interest. We assessed the antidiabetic properties of aqueous extract of C. purpureus shoots (AECPS) and the mechanism of action on pancreatic β-cell dysfunction. Methods: This study was conducted using Thirty-six (36) male Wistar rats. The animals were divided into 6 equal groups, (n = 6) and treatment was performed over 14 days. To induce diabetes in the rats, a single dose of 65 mg/kg body weight of alloxan was administered intraperitoneal along with 5% glucose. In vitro tests such as total flavonoids, phenols, ferric reducing antioxidant properties (FRAP), DPPH, nitric oxide (NO), α-amylase, and α-glucosidase were analyzed. Body weight and fasting blood glucose (FBG) were measured. Biochemical parameters, such as serum insulin, liver glycogen, hexokinase, glucose-6-phosphate (G6P), fructose-1,6-bisphosphatase (F-1,6-BP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and nuclear factor kappa B (NF-ĸB), were analyzed. Additionally, mRNA expressions of phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT), B-cell lymphoma 2 (Bcl-2), and proliferating cell nuclear antigen (PCNA) were each evaluated. Results: This in vitro study showed potency of Cenchrus purpureus extract (AECPS) against free radicals and inhibitory potential as compared with the positive controls. AECPS showed a gradual decrease in alloxan-induced increases in FBG, total cholesterol (TC), triglycerides (TG), low density lipoprotein (LDL-c), G6P, F-1,6-BP, malondialdehyde (MDA), IL-6, TNF-α, and NF-ĸB and increased alloxan-induced decreases in liver glycogen, hexokinase, and high density lipoprotein (HDL-c). The diabetic control group exhibited pancreatic dysfunction as evidenced by the reduction in serum insulin, homeostasis model assessment of β-cell function (HOMA-β), expressions of PI3K/AKT, Bcl-2, and PCNA combined with an elevation in homeostatic model assessment of insulin resistance (HOMA-IR). High performance liquid chromatography (HPLC) revealed 3-O-rutinoside and ellagic acid in AECPS. Conclusion: AECPS showed efficient ameliorative actions against alloxan-induced pancreatic dysfunction, oxidative stress suppression as well as, inflammation, and apoptosis via the activation of PI3K/AKT signaling pathways.